Does fasting in Ramadan ameliorate Lipid profile? A prospective observational study - Akaberi, Arash (Professional Medical Publicaitons, 2014)
Background and Objectives: There are conflicting data on the effects of fasting in Ramadan in Muslim countries on Lipid profile. We aimed to evaluate the effect of fasting on lipid profiles and some ratios which are strong for predicting cardiovascular disease. Methods: This prospective observational study was done in Iran in 2012. Forty three persons were enrolled into the study. Their anthropometric measurement was done. Fasting plasma high density lipoprotein cholesterol (HDL), low density lipoprotein cholesterol (LDL), total cholesterol (TC), and triglyceride (TG) were measured at baseline and after one month fasting during Ramadan by standard methods. Paired t test were used to compare lipid profiles before and after the intervention. Results : High density lipoprotein cholesterol was 33.10±6.53 mg/dL at baseline and increased to 42.49±8.44mg/dL (P <0.001). Fasting in Ramadan decreased serum LDL/HDL and TG/HDL ratios significantly (P <0.001). Triglyceride levels were unaffected. Low density lipoprotein and total cholesterol levels increased (P=0.008). Changes did not differ significantly between men and women. Conclusion: Fasting in Ramadan is effective to ameliorate High density lipoprotein, and LDL/HDL and TG/HDL ratios. Omitting one meal may be considered to control High density lipoprotein level.